Symposium 4: The Spaces of Networked Learning: Symposium Introduction - Bayne, Siân (Proceedings of the International Conference on Networked Learning, 2014)
Education has to date taken surprisingly little account of the so-called 'spatial turn' which has been evident across other areas of the humanities and social sciences in recent decades (Withers, 2009; Guldi, nd). New spatial vocabularies help us shift the assumption that space functions as a ‘static container’ (Fenwick et al, 2011: 129) within which individuals act. Rather, space is increasingly seen as a dynamic entity which is produced by the social and material interactions which take place ‘within’ it. As Fenwick et al (2011) make clear, for forms of education which have to do with media, technology, distance and the online, ‘the ordering of space-time has become a critical influence’. The distancing and networking of education make possible new spatial practices, new patterns of movement and ‘new proximities’ (129). In discussions of online education and the nature of the digital, there has been an historic tendency to see the apparent ‘fluidity’ of 'networked' spaces as inherently liberatory, as providing an educational topology which is somehow freer, more democratic, more ‘open’ simply by virtue of the otherness of ‘cyberspace’ (Bayne, 2004; Edwards et al, 2011). Such discourses continue, influenced now by the promises of democratisation and accessibility-to-all of the ‘open education’ movement (for example Caswell et al, 2008). However, as Edwards et al (2011) point out, ‘Mobility through cyberspaces is neither inherently emancipatory nor positive and relies upon its own immobilities and moorings’ (226): it is important to maintain a critical and broad perspective on the spatial orientations of online education, not simply to privilege the more obviously networked and fluid spaces of the internet. Thus our aim in this symposium is to present various perspectives on the constitution of space in networked learning, in order to come at a critical understanding of the various spatial orientations of education conducted within the multiple social topologies of the internet. Papers will weave a pathway through online higher education, distance education, workplace learning and educational governance, working with the consistent themes of mobility and spatial theory. Our session will combine 2 full papers with 3 short pecha kucha sessions in order to dynamically present a range of different perspectives aimed at stimulating and provoking discussion and debate around the notion of educational space beyond the 'network'.